Synthesis of zinc phthalocyanine containing 1,2-phenylene bis (3-chloropropanoate) substituted groups and investigation of their metabolic enzyme inhibitory effects - Solgun, Derya Gungordu; Sadeghian, Nastaran; Taslimi, Parham; Taskin-Tok, Tugba; Agirtas, Mehmet Salih; Taslimi, Parham; Sadeghian, Nastaran (Pergamon-Elsevier Science Ltd, 2024)
In this study, 4,5-dicyano-1,2-phenylene dinicotinate compound was obtained as a result of the reaction of 4,5dichlorophthalonitrile and nicotinic acid. This compound was reacted with the zinc chloride salt to obtain the original zinc phthalocyanine compound bearing 1,2-phenylene bis(3-chloropropanoate) substituted groups. This compound and its starting material were characterized with the assist of 1 H NMR, IR, UV-vis, Mass spectrum. In the docking study of compounds (3) 3 ) and (4) 4 ) against each target (AChE, BChE, alpha-Amy and alpha-Gly), Zn complex (4) 4 ) exhibits more binding affinity with the target models considered compared to ligand structure (3). 3 ). Especially, AChE protein and complex (4) 4 ) form the best binding affinity with a binding energy value of-10.55 kcal/mol. They are compatible and supportive with the data obtained as a result of in vitro analysis. These 4,5-dicyano-1,2phenylene dinicotinate (3) 3 ) and 2, 10, 16, 24 - tetrakis 1,2-phenylene bis(3-chloropropanoate) phthalocyaninato) zinc(II) (4) 4 ) complexes had effective inhibition against alpha-glucosidase, alpha-amylase, butyrylcholinesterase and AChE. Also, IC50 50 amounts were found as 7.84 and 12.36 mu M for AChE, 3.80 and 4.56 mu M for BChE, 27.08 and 38.14 mu M for alpha-amylase, and 5.30 and 9.73 mu M for alpha-glucosidase.
Keywords: Synthesis; Phthalocyanine; Fluorescence; Enzyme Inhibition; Molecular Docking